The necessary articulation and optimization of the levels of protection of the right to health of older people - Díaz-Tendero, Aída; Dalli Almiñana, María (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
This paper examines the most relevant aspects of the regulation of the right to health for older people at three levels of protection: the universal system (United Nations), the European, Inter-American and African regional systems, and the Spanish legal system. The analysis considers not only the normative texts that specifically recognise the right to health for older persons, but also those that, in the absence of specific regulations, foresee the protection of health in a generic manner. In light of this study, we conclude that it’s necessary to adopt both a universal convention and a comprehensive national law to protect the right to health and the other rights of this age group, and that these regulations must take into account the provisions of current regional instruments.
Keywords: right to health; older persons; levels of protection; non-discrimination